2022
DOI: 10.1007/s10753-021-01586-w
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Alleviates Hepatic Fibrosis in Associated with Decreased Endoplasmic Reticulum Stress-Mediated Apoptosis and Inflammation

Abstract: Abstract—Hepatic fibrosis (HF) is the typical response to chronic liver disease and is characterized by deposition of abundant extracellular matrix. The aim of the present study was to investigate the protective effect of resveratrol (RSV) in a CCl4-induced rat model of HF. We demonstrate that the administration of RSV effectively improves liver function and ameliorates liver fibrosis by reducing collagen deposition and reversing the expression of COL1A1 and PPAR-γ. Treatment efficacy of RSV could be attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Other strategies targeting oxidative stress were based on the inhibition of NADPH, such as GKT137831 [ 161 ], angiotensin blocking agents (discussed in functional targets below). Resveratrol, a natural anti-oxidant with multiple effects on vascular biology, has also been found to decrease portal pressure, decrease fibrosis, and improve NO availability in rats with experimental cirrhosis [ 47 , 162 ].…”
Section: Therapeutic Agents For Liver Cirrhosis and Portal Hypertensionmentioning
confidence: 99%
“…Other strategies targeting oxidative stress were based on the inhibition of NADPH, such as GKT137831 [ 161 ], angiotensin blocking agents (discussed in functional targets below). Resveratrol, a natural anti-oxidant with multiple effects on vascular biology, has also been found to decrease portal pressure, decrease fibrosis, and improve NO availability in rats with experimental cirrhosis [ 47 , 162 ].…”
Section: Therapeutic Agents For Liver Cirrhosis and Portal Hypertensionmentioning
confidence: 99%
“…As well as protecting cells from oxidative stress, resveratrol also promotes the expression of antioxidative enzymes and their substrates ( Miguel et al, 2021 ; Santos et al, 2021 ). Recently, it has been suggested that resveratrol has hepatoprotection properties through its anti-inflammatory and antioxidant effects ( Chupradit et al, 2022 ; Ma et al, 2022 ; Tong et al, 2022 ). It has also been reported that resveratrol attenuates acetaminophen toxic metabolite N-acetyl-p-benzoquinone-imine and facilitates liver regeneration by modulating the silent mating type information regulation two homolog (SIRT1), tumor protein P53, and Tumor Necrosis Factor-alpha (TNF-α) ( Sener et al, 2006 ; Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that resveratrol can prevent or slow the progression of various brotic diseases, including cardiac brosis [9], pulmonary brosis [10], renal brosis [11], prostate brosis [12] and systemic sclerosis [13]. In liver brosis, resveratrol provides signi cant protection against brosis induced by carbon tetrachloride (CCl 4 ) [14,15], dimethylnitrosamine [16], bile duct ligation [17], and Schistosoma japonicum [18]. In fact, resveratrol reduces portal pressure, HSC activation, in ammatory cell in ltration of liver tissue, and brosis and improves hepatic endothelial function in cirrhotic rats [19].…”
Section: Introductionmentioning
confidence: 99%
“…In liver fibrosis, resveratrol provides significant protection against fibrosis induced by carbon tetrachloride (CCl 4 ) (Li, Zhang, Zhan, & Zheng, 2021; Ma et al, 2022), dimethylnitrosamine (Abdu & Al-Bogami, 2019), bile duct ligation (ShamsEldeen et al, 2021), and Schistosoma japonicum (Chen et al, 2019). In fact, resveratrol reduces portal pressure, HSC activation, inflammatory cell infiltration of liver tissue, and fibrosis and improves hepatic endothelial function in cirrhotic rats (Izzo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation